The PPP hypothesis revisited: Evidence using a multivariate long-memory model - Guglielmo Maria Caporale; Luis A. Gil-Alana; Yuliya Lovcha (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper examines the PPP hypothesis analysing the behaviour of the real exchange rates vis-à-vis the US dollar for four major currencies (namely, the Canadian dollar, the euro, the Japanese yen and the British pound). An innovative approach based on fractional integration in a multivariate context is applied to annual data from 1970 to 2011. Long memory is found to characterise the Canadian dollar, the British pound and the euro, but in all four cases the results are consistent with the relative version of PPP.
Keywords: C22; F31; 330; PPP; long memory; multivariate fractional integration